Assignment Again! Investigating the Psychological Perspectives of Assignment and Assignment Deadlines among Tertiary Level Students - Mir, Shantona; Roy, Sukanto (English Language Teaching Perspectives, 2024)
This paper aims to study university students' psychological perspectives on assignment deadlines. The purpose of this study is to investigate the issues faced by students before assignment submission and their relation to the education system, programme of study, personalities of teachers, and the importance of assignments. All in all, this paper delves into students' psychological barriers regarding assignments and the problems teachers face while assigning assignments. A mixed method is applied to conduct the research. The quantitative data has been collected using a survey among students from 8 different universities, and the qualitative data has employed interviews with teachers from 2 different universities. Procrastination, task management, pressure, and stress have been found to play the greatest role in facilitating the obstacles students face while completing an academic task. From the collected data, it is also recorded that students take into account multiple factors when it comes to assignments and their deadlines, i.e., not enough practical knowledge gain, the teaching style of the teacher, length of the assignment, time allocation, methods used in different programme of study, lack of interest in a course, demotivation, discouragement, and hard courses. A common view among the interviewees is that teachers’ lack of exposure to technology and deficient knowledge of teaching may be the reasons that students develop such attitudes toward assignments. In addition, this paper also addresses feasible solutions and recommendations to this very issue for the betterment of students and enhancing the education system.